Determinants of Menstrual Health in Young Women Living in Darussalam Islamic Boarding School - Misniarti; Sutriyanti, Yanti; Haryani, Sri (Jurnal Kebidanan Besurek, 2022)
Background: Adolescence is also called a transitional period starting with children showing signs of pubertal development and continuing with changes from non-sexual to sexual. During menstruation, young women may face various problems related to menstrual disorders. The respondent in MTS school is 194 who live in Pondok Pesantren Darussalam. The government has a policy on reproductive health in adolescents which is listed in Law No. 23 of 1992 concerning health, in which the government makes preventive and promotive efforts. Nursing models of health belief models can be used to see the health of puberty in young women. Based on the description above, the researcher is interested in researching "the determinants of menstrual health in young women living at Darussalam Islamic Boarding School, Kepahiang Regency in 2017. Objective: To determine the determinants of menstrual health for young women living in Darussalam Islamic boarding schools. Method: Analytical descriptive method using a cross-sectional approach. The population in this study was 194 people. The location of research at the Darussalam Islamic Boarding School, Kepahiang Regency, which was held from October to December. Sampling used the Purposive Sampling method. The research instrument was the Chi questionnaire. Results: there is a relationship between perceptions of vulnerability and perceived barriers to health behavior during menstruation in young women living in Pondok Pesantren Darussalam, and there is no relationship between perceived vulnerability and health behavior during menstruation in young women living in Pondok Pesantren Darussalam. Suggestion: the results of this study can be used as a source of information for public health to add information about health education during menstruation at the UKS activities at the Darussalam Islamic Boarding School.